EFFECTS OF FLUSHING AND MILK REPLACER ON IMPROVING THE PRODUCTIVITY OF DAIRY BUFFALOES AND THEIR CALVES - Aquino, Daniel L.; Del Rosario, Wilma T.; Verona, Lester S.; Delizo, Mario M. (Proceeding Buffalo International Conference, 2013)
The effects of flushing and milk replacer on improving the productivity of buffaloes and calves were evaluated. In flushing, eighteen pregnant Bulgarian buffaloes were given 2-4 kg concentrates one month before calving up to two months post-calving. Eighteen nursing calves borne by the cows subjected to flushing were fed with milk replacer for 90 days. The daily milk ration of calves composed of 640 grams milk powder dissolved in 4 liters warm water (38-40oC).This was divided into two with 2 liters each for morning and afternoon meals. Flushing improved the total milk production of cows from 1,330 kg to 1,654.6 kg with longer lactation period from 260 to 270 days. This was equivalent to 6.0 kg milk/day which was one kg higher than the cows without flushing (5.0 kg). The flushed cows exhibited post-partum estrus as early as 47 days. At 127 days service period using artificial insemination, 70% of the cows were confirmed pregnant. With flushing, the calving interval of cows was reduced from 18.4 months to 14.8 months. A net income of P33,532.35 was achieved due to improved milk production and reproduction of the animals. Feeding milk replacer to calves gave 588 grams ADG with no health problems observed. It gave a daily feed cost savings of P38.40/calf or P2, 520.00 in 90 days feeding. Milk replacer is a practical and economical substitute to raw milk because it enhanced rumen development and early weaning of calves.